STRATEGI PEMASARAN BATIK MADURA DALAM MENGHADAPI PEMASARAN GLOBAL - Rusnani, Rusnani; Andini, Isnani Yuli (Fakultas Ekonomi, 2014)
Batik Madura Company Madura representing small company, expanding many in archipelago of Madura among others of Pakandangan Sumenep area, Banyumas Pamekasan area, and Tanjung Bumi of Bangkalan area, become every Sub-Province in Archipelago of Madura have batik Centre owning separate individuality, because batik of Madura represent small company, even home industry, for that mount its marketing less maximal, so that its marketing area only in local level, thereby less recognized for society, for that need professional handling to be batik of Madura can be famous and compete either in local marketing, national and also in global, with other batiks, by using appropriate marketing strategy. Long-range target of this research is batik Madura company can market batik of Madura is globally. Special target of this research is to repair batik of Madura marketing system by giving correct marketing strategy, which conducted by entrepreneur in marketing batik of Madura and introduce Batik of Madura to wide of society. This Research type use descriptive qualitative approach with aim to give objectively picture regarding accurate by using documentation method and field study. SWOT analysis conducted that batik of Madura have strength of uniq product so that there is opportunity to market to broader area even to global level although its weakness is less in promotion level. In this research of appropriate strategy for the batik of Madura is use aggresive strategy (attacking), that is by exploiting strength had to fill high opportunity. Keyword : Marketing Strategy, Batik of Madura, Global Marketing